Measuring changes in diet deprivation: New indicators and methods - Pauw, Karl; Ecker, Olivier; Thurlow, James; Comstock, Andrew R. (Elsevier, 2023)
Improving diet quality is an emerging development policy priority. Existing indicators emphasize the cost and affordability of healthy diets but have not attempted to measure how far households are from ideal diets or how policies may nudge them closer to them. We propose a new Reference Diet Deprivation (ReDD) index, estimated from household consumption survey data, that measures the incidence, breadth, and depth of diet deprivation across multiple food groups. While informative as a standalone measure, we demonstrate how the ReDD index can be integrated into an economic model to examine changes in diet quality under different policy or external shocks. Our Nigerian case study shows that productivity growth in the dairy, pulse & nut, fruit, and red meat value chains have more potential than staple crops to reduce diet deprivation. While these findings have implications for food and agricultural policy prioritization in Nigeria, the study more importantly demonstrates the usefulness of the ReDD index for assessing diet quality and examining the drivers of dietary change when used in conjunction with a simulation model.